1996
DOI: 10.3354/meps134295
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways

Abstract: The unique predominance of oleyl alcohols enzyme underlying the de novo formation of wax (18:l) is the striking characteristic of the lipids of the Antarcesters (and also triacylglycerols) is the Tlrpe-1 fatty acid tic euphausiid Thysanoessa macrura. The 2 isomers 18:l(n-9) synthetase, which present in all animals studied so moieties, whereas the wax esters of herbivorous speand 1 6 0 , which, along with the monounsaturate 18:l(n-g), accounted for more than 80'v0 of the total fattv acids, Phosties,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In the Antarctic euphausiid Thysanoessa macrura, lipids decreased from 40 to 9%DM (Sep to Nov) after reproduction was completed. The lipid utilized was not replaced until the phytoplankton bloom later in the year (Hagen et al 1996, Hagen & Kattner 1998. Similarly, female C. hyperboreus had a winter/early spring spawn during which lipids decreased from 50 to 25%DM (Conover & Corner 1968).…”
Section: Accumulation and Utilization Of Storage Lipids Reproductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the Antarctic euphausiid Thysanoessa macrura, lipids decreased from 40 to 9%DM (Sep to Nov) after reproduction was completed. The lipid utilized was not replaced until the phytoplankton bloom later in the year (Hagen et al 1996, Hagen & Kattner 1998. Similarly, female C. hyperboreus had a winter/early spring spawn during which lipids decreased from 50 to 25%DM (Conover & Corner 1968).…”
Section: Accumulation and Utilization Of Storage Lipids Reproductionmentioning
confidence: 99%
“…In addition, E. crystallorophias also contained considerable amounts of phytol at one under-ice location in Antarctica (Falk-Petersen et al 1999). The fatty alcohol composition of the Antarctic euphausiid Thysanoessa macrura is unique because it has both 18:1(n-9) and (n-7) as its principal alcohols (Kattner et al 1996, Hagen & Kattner 1998. Kattner & Krause (1989) reported 22:1 alcohol to account for 43 to 72% of the alcohols in Calanus finmarchicus from the North Sea, whereas Miller et al (1998) reported an absence of this alcohol in C. finmarchicus from the Gulf of Maine.…”
Section: Fatty Alcoholsmentioning
confidence: 99%
See 3 more Smart Citations